Pengaruh Pelaksanaan Interprofessional Collaboration Practice dan Waktu Tunggu Pasien terhadap Kepuasan Melalui Kualitas Pelayanan : Studi pada Rumah Sakit Lavalette Malang - Chamariyah Chamariyah; Sherly Nurwiyanti Anwar; Wasis Budiarto (Universitas 45 Surabaya, 2024)
Sherly Nurwiyanti Anwar, 2024. The Effect of Implementing Interprofessional Collaboration Practice and Patient Waiting Time on Satisfaction Through the Service Quality (Study of Lavalette Hospital Malang), Wijaya Putra University Postgraduate Program. The type of research is explanatory, namely the level of explanation, namely how the variables studied will explain the object being studied through the data collected. The research approach used was quantitative, the research sample was 92 respondents. Data analysis uses SEM PLS analysis. The aims of this research are: 1) To describe the implementation of interprofessional collaboration practice, patient waiting time, service quality, and satisfaction at Lavalette Hospital Malang; 2) To test and analyze the influence of interprofessional collaboration practice on service quality at Lavalette Hospital Malang; 3) To test and analyze the effect of patient waiting time on the service quality at Lavalette Hospital Malang; 4) To test and analyze the effect of interprofessional collaboration practice on satisfaction at Lavalette Hospital Malang; 5) To test and analyze the influence of service quality on patient satisfaction at Lavalette Hospital Malang; 6) To test and analyze the effect of patient waiting time on satisfaction at Lavalette Hospital Malang; 7) To test and analyze the indirect effect of interprofessional collaboration practice on satisfaction at Lavalette Hospital Malang which is mediated by the service quality. The research results show that: 1) The implementation of interprofessional collaboration practice has a direct and significant positive effect on the quality of patient care with a path coefficient value of 0.565 and a p-value of 0.001; 2) Patient waiting time has a direct and significant positive effect on the quality of patient service with a path coefficient value of 0.346 and a p-value of 0.000; 3) The implementation of interprofessional collaboration practice has a direct and significant positive effect on patient satisfaction with a path coefficient value of 0.333 and a p-value of 0.001; 4) The quality of patient service has a direct and significant positive effect on patient satisfaction with a path coefficient value of 0.589 and a p-value of 0.000; 5) Patient waiting time has a positive but not significant direct effect on patient satisfaction with a path coefficient value of 0.060 and a p-value of 0.418; 6) The implementation of interprofessional collaboration practice has a significant positive indirect effect on patient satisfaction which is mediated by the quality of patient service with a path coefficient value of 0.333 and a p-value of 0.000; 7) Waiting time has a significant positive indirect effect on patient satisfaction which is mediated by the quality of patient service with a path coefficient value of 0.333 and a p-value of 0.000.